Encapsulated Fecal Microbiota Transplantation: Development, Efficacy, and Clinical Application - Halaweish, Hossam F.; Boatman, Sonja; Staley, Christopher (Frontiers in Cellular and Infection Microbiology, 2022)
Fecal microbiota transplantation (FMT) has been established as a highly restorative therapeutic approach for treating recurrent Clostridioides difficile infection (rCDI). Recently, the use of capsule-based fecal microbiota transplantation (cFMT) has been shown to be a clinically effective approach to restore intestinal microbiota composition. This convenient, oral delivery provides an easy route of administration and a newfound flexibility for clinicians and patients. In this review, we discuss the development of cFMT, paying particular attention to lyophilized cFMT products. We review the available published clinical studies comparing cFMT with lower endoscopic FMT (eFMT) or placebo. We further discuss the pharmacokinetics of FMT, which should be understood in a framework of microbial ecology that considers the complex and dynamic interactions of gut microbiota with host factors and other microorganisms. Promisingly, the results of multiple trials investigating cFMT vs. eFMT in rCDI show cFMT to be as effective as eFMT at preventing rCDI. However, its efficacy in non-rCDI conditions, including obesity and metabolic syndrome, inflammatory bowel disease, HIV, and neurologic conditions, is less clear and more research is needed in these areas. Standardization of formulation, dose, and timing of administration to ensure optimal microbiota engraftment and clinical response is also a challenge to be addressed. Overall, cFMT is a practical method for fecal microbiota transplantation, with similar efficacy to eFMT in the resolution of rCDI, that holds therapeutic potential in a variety of other diseases.